2018
DOI: 10.1111/gcb.14446
|View full text |Cite
|
Sign up to set email alerts
|

Temperature niche position and breadth of ectomycorrhizal fungi: Reduced diversity under warming predicted by a nested community structure

Abstract: Species with narrow niche breadths are assumed to be more susceptible to environmental changes than those with wide niche breadths. Although information on niche properties is necessary for predicting biological responses to environmental changes, such information is largely missing for soil microbes. In this study, we present the temperature niche positions and breadths of a functionally important group of eukaryotic soil microbes, ectomycorrhizal (EM) fungi. We compiled high-quality EM fungal sequence data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 65 publications
(85 reference statements)
3
34
1
Order By: Relevance
“…The lineage-level taxonomic composition of EcM fungi is consistent with previous comprehensive root-tip-based surveys in temperate Eurasia and North America, where forests of Pinaceae or Fagales dominate (Tedersoo et al, 2012a;Miyamoto et al, 2018;van der Linde et al, 2018). The overall commonness of/inocybe lineage and low abundance of/cortinarius, the rhizomorph-forming group and most species-rich EcM fungal genus in the Nordic countries (Knudsen and Vesterhold, 2012), is somewhat unexpected.…”
Section: Ectomycorrhizal Fungisupporting
confidence: 84%
“…The lineage-level taxonomic composition of EcM fungi is consistent with previous comprehensive root-tip-based surveys in temperate Eurasia and North America, where forests of Pinaceae or Fagales dominate (Tedersoo et al, 2012a;Miyamoto et al, 2018;van der Linde et al, 2018). The overall commonness of/inocybe lineage and low abundance of/cortinarius, the rhizomorph-forming group and most species-rich EcM fungal genus in the Nordic countries (Knudsen and Vesterhold, 2012), is somewhat unexpected.…”
Section: Ectomycorrhizal Fungisupporting
confidence: 84%
“…For example, some fungal taxa preferred to nutrient-rich habitats, while some taxa could grow well in nutrient-poor habitats (Cox et al, 2010;Mundra et al, 2016). In addition, some fungi only distributed in habitats with lower MAT and exhibited narrower temperature breadths, while some fungi were detected across wider temperature ranges and in warmer habitats (Miyamoto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…different niche properties including nutrients and climate (Cox et al, 2010;Mcguire et al, 2010;Mundra et al, 2016;Barnes et al, 2018;Miyamoto et al, 2018). For example, some fungal taxa preferred to nutrient-rich habitats, while some taxa could grow well in nutrient-poor habitats (Cox et al, 2010;Mundra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The richness of EcMF communities decreases with increasing atmospheric temperature [113,114]. Analysis of the EcMF temperature niche position on the Japanese archipelago revealed that the richness and diversity of the EcMF community are highest in cold regions; this further indicates that climate warming might limit the distribution of EcMF only adapted to the cold climate and thus reduce EcMF diversity [113]. However, there exist considerable differences in the temperature sensitivity and temperature adaptability among various EcMF taxa.…”
Section: The Impact Of Environmental Change On Ecmfmentioning
confidence: 99%